David W. Hogue: A Biography - Skoch, Martha J. (My University, 1987)
This biographical study is concerned with the life and contributions of Dr. David W. Hogue, Dean of Student Affairs 1968-present, to the area of student affairs at the University of Wisconsin-La Crosse. The primary purpose of this study was to present the life and career of Dr. David W. Hogue through a combination of written, audio, and visual means. A video-tape recorded interview with Dr. Hogue, Dr. Reid Horle, Mrs. Sis Hogue, and the researcher was held in Dean Hogue's office with the assistance of the University of Wisconsin- La Crosse Audio-visual Department. Dean Hogue was graduated from Wisconsin State Teacher's College, La Crosse with a Bachelor of Science in Education degree and from the University of Wisconsin at Madison with a Master of Science degree in educational administration. In 1964, Dean Hogue completed his doctorate degree at the University of Northern Colorado. Eleven years of teaching and administrative experience provided him with a background of knowledge which he brought to the La Crosse campus in 1960. Dean David W. Hogue exemplified his genuine concern through his contributions to students and student affairs at the University of Wisconsin-La Crosse. For twenty-six years, Dean Hogue served the University and assisted in the growth and development of the Student Affairs Unit as well as the development and implementation of the college student personnel program.

This biographical study is concerned with the life and contributions of Dr. David W. Hogue, Dean of Student Affairs 1968-present, to the area of student affairs at the University of Wisconsin-La Crosse. The primary purpose of this study was to present the life and career of Dr. David W. Hogue through a combination of written, audio, and visual means. A video-tape recorded interview with Dr. Hogue, Dr. Reid Horle, Mrs. Sis Hogue, and the researcher was held in Dean Hogue's office with the assistance of the University of Wisconsin- La Crosse Audio-visual Department. Dean Hogue was graduated from Wisconsin State Teacher's College, La Crosse with a Bachelor of Science in Education degree and from the University of Wisconsin at Madison with a Master of Science degree in educational administration. In 1964, Dean Hogue completed his doctorate degree at the University of Northern Colorado. Eleven years of teaching and administrative experience provided him with a background of knowledge which he brought to the La Crosse campus in 1960. Dean David W. Hogue exemplified his genuine concern through his contributions to students and student affairs at the University of Wisconsin-La Crosse. For twenty-six years, Dean Hogue served the University and assisted in the growth and development of the Student Affairs Unit as well as the development and implementation of the college student personnel program.
Keywords: Education, Higher -- Wisconsin -- La Crosse -- History; University of Wisconsin-La Crosse -- History; Hogue, David W.